Evaluation of intermittent protocol at incremental laboratory test in measuring physiological indices of soccer players - Atta Bahreini Nejad; ِDariush Moflahi; Mehdi Abbaspour (Shahid Beheshti University, 2022)
Purpose: Due to the intervals' nature of soccer, the aim of this study was to evaluate intermittent protocol of incremental laboratory test in measuring the physiological parameters of soccer players.Methods: Eighteen young soccer players (Mean ± SD; age 16.78 ± 0.78 years, weight 61.33 ± 9.44 kg, height 177 ± 6.75 Cm) voluntarily participated into two incremental laboratory tests (continuous and intermittent protocol) on the HP Cosmos Treadmill with 48-hour interval and then Bangesbo field test was performed. The subjects' cardiopulmonary parameters were measured by gas analyzer, metalyzer3b model, and blood lactate before and after the tests with lactometer Scout model. Statistical analysis was performed by ANOVA Repeated Measure, paired t-test and Pearson correlation coefficient at the significant level P ≤ 0.05.Results: There was no significant difference between the physiological factors of continuous and intermittent tests, but there was a significant difference between the distance at continuous and intermittent tests (P = 0.031). There was a significant positive relationship between the performance of the Bangesbo test with the maximum oxygen consumption (r = 0.64, P= 0.011) and distance (r = 0.62, P = 0.018) of the intermittent test.Conclusion: The significant positive correlation between the maximum oxygen consumption of the intermittent test and the performance of the Bangesbo test, Higher distance in intermittent test and significant positive correlation between performance of Bangesbo test and distance of intermittent incremental test; It may be explained by the similarity of the intermittent test to the interval component of the playing soccer and this observing suggest to consider component of athlete's activity when defining the incremental test.